Comparison of Different Turbulence Models in Predicting Separated Flow over an Airfoil (University of Khartoum Engineering Journal, 2022)
Fluid flow around a NACA 4412 airfoil in a wind tunnel test section at Reynolds number of 3 x 106, based on the chord of the airfoil (150 mm) and free stream velocity (30 m/s), is considered. The study covers the boundary layers around the airfoil and the wake region at different angles of attack. Different turbulence models are used to predict separated flows over the airfoil. Two-equation turbulence models, k-ω and k-ε, and ReynoldsStress Model are tested for the ability to predict boundary layer separation on the airfoil. Reynolds Stress model captured the physics of separated flow favourably, and gave a very realistic evolution of the vortex formed due to separation. Statistics of the flow which is generated by RSM are in good agreement with an existing wind tunnel experimental data. The flow field which is generated by the two-equation turbulence models poorly predictedflow separation and vortex dynamics and consequently overestimated the lift coefficient for angles of attack larger than the critical angle of attack.